The Effect of Remuneration on Lecturer Performance in Gorontalo State University - Melki Ramon Amati; Heldy Vanni Alam; Valentina Monoarfa (Journal of International Conference Proceedings (JICP), 2018)
The Tri Dharma of higher education is the three basic pillars of mindset and being obligations for lecturers in order to produce student output as intellectuals. Higher education as one of the formal institutions is demanded to provide quality education services in accordance with the mandate, laws and stakeholder expectations. Lecturer as the spear of the success of education at the college level is always required to provide maximum service and professional graduates quality too. The purpose of this study was to determine the effect of remuneration on Lecturer Performance at Gorontalo State University. This type of research is survey using a quantitative approach. Data collected in the form of primary data by distributing questionnaires to 47 lecturers at environment of the Faculty of Economics, Gorontalo State University. Next is the data collected was processed with the help of SPSS 21 program and analyzed using simple linear regression. Research results show that remuneration contributes towards improving the performance of lecturers at the Faculty of Economics, State University Gorontalo. This is in accordance with the government's expectations that the purpose of the gift. One of them is remuneration to increase work productivity. If the productivity work increases, it is automatically affected the improved performance. Keywords: Remuneration, Lecturer Performance